2019
DOI: 10.2478/sjecr-2019-0077
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of N-Methyl-D-Aspartate Receptor Blockade on Oxidative Status in Heart During Conditioning Maneuvers

Abstract: N-methyl-D-aspartate receptor (NMDAR) belongs to iono-tropic glutamate receptor family. The most prominent roles of the NMDAR are related to the physiological and pathophysiological processes of the central nervous system (CNS). The link between NMDAR and cardiovascular pathology came into focus due to detrimental effects of homocysteine on the cardiovascular system. Regarding the fact that NMDAR affects Ca2+ homeostasis in cells, one of the main mechanisms which mediate adverse effects of glutamate dyshomeost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Another part of the experimental protocol was dedicated to the assessment of the role of NMDAR activity in the production of oxidative species and oxidative stress. The preliminary results regarding the effects of MK-801 on oxidative stress biomarkers have been partially published [30]. One of the major mechanisms mediating in the deleterious effects of ischemia and reperfusion is oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another part of the experimental protocol was dedicated to the assessment of the role of NMDAR activity in the production of oxidative species and oxidative stress. The preliminary results regarding the effects of MK-801 on oxidative stress biomarkers have been partially published [30]. One of the major mechanisms mediating in the deleterious effects of ischemia and reperfusion is oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…TBARS-index of lipid peroxidation measured as TBARS; H 2 O 2 -hydrogen peroxide; TG-(RS)-(Tetrazol-5-yl)glycine; preC-preconditioning; postC-postconditioning. Some results regarding the effects of MK-801 on oxidative balance have been partially published[30] as a preliminary report. Statistical significance between points of interest was presented as: a-in control group; b-in glutamate group; c-in TG group; d-in memantine group; e-in MK-801 group.…”
mentioning
confidence: 99%
“…It has been demonstrated that NMDA activation is associated with increased intracellular calcium, impairment of nitric oxide synthesis, and increased production of reactive oxygen species, and is the one of the key causes in pathogenesis of heart failure (Kang et al 2009;Seminotti et al 2011;Martins-Pinge et al 2013;Stern and Potapenko 2013;Moura et al 2014). The role of NMDA activation in the pathogenesis of ischemic/reperfusion injury has been confirmed by the cytoprotective effect of the NMDA inhibition, especially, in pre-and postconditioning of the isolated rat heart (Weinberg et al 2016;Govoruskina et al 2019).…”
Section: Discussionmentioning
confidence: 93%